The Effectiveness of the Angklung Bina Nusantara Application in Improving the Musicality of Students of the Madrasah Ibtidaiyah Teacher Education Study Program - Bagus Indrawan; Nur Isnaini (Civiliza Publishing, Indonesia., 2026)
Students of the Madrasah Ibtidaiyah Teacher Education Study Program often have diverse musical backgrounds, and many of them have limited experience in playing musical instruments. The limited availability of traditional musical instruments, such as the angklung, increases the barriers to students' independent practice. This study aims to analyze the effectiveness of the Bina Nusantara Angklung implementation in improving the musical abilities of students in the Elementary Madrasah Teacher Education Study Program. The research approach used is quantitative research with a pre-experimental design, conducting a pretest-posttest. The participants were of students of the Madrasah Ibtidaiyah Teacher Education Study Program who took the Cultural Arts course in the odd semester of the 2025/2026 academic year. Data were collected through performance observation sheets based on three musicality indicators: pitch accuracy, rhythmic accuracy, and group harmonization. The data were analyzed using descriptive statistics and a paired sample t-test. The findings show that the use of the Angklung Bina Nusantara application improved students’ musicality skills. Before the course, 63% of students had low musical ability. After the course using the app, 83% of students had good or excellent musical ability. Furthermore, the app encouraged independent practice, increased self-confidence, and supported collaborative learning. These findings suggest that the Angklung Bina Nusantara app can be used as an effective digital learning tool to improve students' musical abilities while supporting the preservation of traditional music in higher education.